2019
DOI: 10.1177/1526924819855357
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable Risk Factors for Delayed Graft Function After Deceased Donor Kidney Transplantation

Abstract: Purpose: Delayed graft function is a major complication after kidney transplantation affecting patients’ long-term outcome. The aim of this study was to identify modifiable risk factors for delayed graft function after deceased donor kidney transplantation. Methods: This is a single-center retrospective cohort study of a university transplantation center. Univariate and multivariate step-wise logistic regression analysis of patient-specific and procedural risk factors were conducted. Results: We analyzed 380 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 26 publications
2
19
0
2
Order By: Relevance
“…Our data are closely related to those reported by Gingell-Littlejohn et al [11] and Kaufmann et al [9]. Both studies identified a correlation between intraoperative MBP and DGF occurrence, despite targets and cut-offs varied between studies [any recorded MBP<70 mmHg and an MBP <80 mm Hg at the time of reperfusion, respectively].…”
Section: Plos Onesupporting
confidence: 91%
See 3 more Smart Citations
“…Our data are closely related to those reported by Gingell-Littlejohn et al [11] and Kaufmann et al [9]. Both studies identified a correlation between intraoperative MBP and DGF occurrence, despite targets and cut-offs varied between studies [any recorded MBP<70 mmHg and an MBP <80 mm Hg at the time of reperfusion, respectively].…”
Section: Plos Onesupporting
confidence: 91%
“…No guideline or recommendation is to date available for catecholamine choice/ dosage [15,23] as for intraoperative fluid amount and quality [24][25][26]. On the other hand, the excessive use of inotropes [27] and fluid infusions [9], as observed in our population, were both associated with adverse outcomes. A "goal-directed therapy," borrowed from critical care experience [28,29], may represent the optimal approach in this setting, although no studies are currently available in KTs [15].…”
Section: Plos Onementioning
confidence: 79%
See 2 more Smart Citations
“…19 Diuretic treatment was identified as predisposing factor in 33% of patients. Apart from rejection, typical etiologies of posttransplantation kidney injury are hemodynamic-mediated 20,21 or caused by ischemia-reperfusion damage. 22…”
Section: Delayed Graft Functionmentioning
confidence: 99%